Continuous Professional Development (CPD) Expectations of Secondary School Teachers : A Pilot Study in Kendrapara and Cuttack Districts of Odisha - Senapati, Ratikanta; Singh, Sunil Kumar (JOURNAL OF INDIAN EDUCATION, 2023)
Continuous Professional Development (CPD) is a continuous and systematic process by which in-service teachers enhance their professional knowledge, capabilities, and skills with time to cope with new and changing roles and new approaches to teaching. Any CPD programme should be intentional, on-going and systematic in nature. From the studies of Tewari (2016); Singh, Patel and Mishra (2019); Tyagi and Mishra (2021), it was found that most of the CPD programmes were organised without knowing the actual need of teachers. In the present pilot study, an online survey was conducted on 54 secondary school teachers from Kendrapara and Cuttack districts of Odisha by using convenience sampling method. A questionnaire comprising 14 items was used for obtaining the data. The items were designed to collect two-fold information from teachers, namely (i) their previous experience of participation in the CPD programme, and (ii) their further expectations from CPD courses. The results of this pilot study revealed that only 48 per cent of teachers had participated in any CPD programmes during their service. This study also revealed that the respondent teachers wanted to include skills like academic supervision and management, communication, child psychology, laboratory activity related skill and guidance counseling in their on-going CPD programmes. Also, they were very much interested to include activities or practices like remedial teaching, workshop for workload management and professional enhancement, training on continuous online assessment in their CPD programmes. The details of this pilot study have been given in this paper.